Vigabatrin-Associated "Acute Encephalopathy" - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A 6-month-old girl with Alexander disease and hydrocephalus, treated at Children's Hospital, Tubingen, Germany, developed acute encephalopathy within 3 days of starting vigabatrin (VGB).